Fee for the use of permits to sell alcoholic beverages during the Covid-19 pandemic - Małgorzata Szalewska (Prawo Budżetowe Państwa i Samorządu)
A fee for using the permit to sell alcoholic beverages is a financial instrument which charges the entrepreneur who has been granted the permission to sell alcoholic beverages. The creation of a legal situation on the part of the entrepreneur entitling this entrepreneur to lawfully distribute alcoholic beverages is the subject to the fee’s obligation. That subject is synonymous with the use of the permit. The essence of the fee in question should be sought in the participatory model. Under this model the entity which is granted the right to sell alcoholic beverages contributes to covering the costs of eliminating the negative social effects of alcohol consumption. Business activity’s restrictions which have been introduced in connection with the SARS-Cov-2 epidemic put a question mark over the material basis for the obligation to pay the said fee. These restrictions in fact constitute a temporary revocation of the right to sell alcoholic beverages intended for a consumption at the point of sale. The solutions adopted by the legislator, consisting of an facultative authorisation of the municipal authorities to exempt the entrepreneurs from the obligation to pay the fee, should be deemed inadequate to the practical implications of the outbreak of the pandemic.